2016
DOI: 10.1109/tmm.2016.2574623
|View full text |Cite
|
Sign up to set email alerts
|

Do Personality and Culture Influence Perceived Video Quality and Enjoyment?

Abstract: The interplay between system, context and human factors is important in perception of multimedia quality. However, studies on human factors are very limited in comparison to those for system and context factors. This article presents an attempt to explore the influence of personality and cultural traits on perception of multimedia quality. As a first step, a database consisting of 144 video sequences from 12 short movie excerpts has been assembled and rated by 114 participants from a cross-cultural population.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 61 publications
4
33
0
Order By: Relevance
“…It has been shown that user factors can explain more of the variance in user ratings than the system factors [4], [9]. In the context of video watching experiences, social context and demographic factors [5], and personality and culture traits [6] have an impact on QoE. With respect to context, studies have looked at physical surroundings (e.g.…”
Section: B Effect Of Context and User Factors On Qoementioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that user factors can explain more of the variance in user ratings than the system factors [4], [9]. In the context of video watching experiences, social context and demographic factors [5], and personality and culture traits [6] have an impact on QoE. With respect to context, studies have looked at physical surroundings (e.g.…”
Section: B Effect Of Context and User Factors On Qoementioning
confidence: 99%
“…The method has recently been extended to integrate the encoding resolution and video size automatically [3]. Including user factor besides system factors has been used to improve the accuracy of models predicting QoE for video watching scenarios [6], [50]. To our knowledge there are no models for predicting the QoE in multi-party videoconferencing based on video quality, nor any that consider user factors and interaction for an increased accuracy.…”
Section: Prediction Of Videoconferencing Qoementioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, they cannot be part of real-time applications such as video transmission systems. Second, their results depend on the observers' physical conditions, personality, and emotional state [26]. Therefore, the development of objective VQA methods that are able to predict the perceptual quality of visual signals is essential.…”
Section: Introductionmentioning
confidence: 99%
“…Hammeed et al [2] and Jang et al [6] put great efforts into converting problems of subjective video quality assessment into computational ones. Scott et al improved the computational model by considering personality and cultural influences [19]. Computational quality evaluation models have shown effectiveness in applications such as online video recommendations [1], communications [2] and video editing [20].…”
Section: Related Workmentioning
confidence: 99%